Macrophage Migration Inhibitory Factor (MIF) and Manganese Superoxide Dismutase (MnSOD) as early predictors for survival in patients with severe sepsis or septic shock - Brenner, Thorsten; Hofer, Stefan; Rosenhagen, Claudia; Steppan, Jochen; Lichtenstern, Christoph; Weitz, Jürgen; Bruckner, Thomas; Lukic, Ivan K.; Martin, Eike; Bierhaus, Angelika; Hoffmann, Ursula; Weigand, Markus A. (Journal of surgical research, 2010)
Background - Severe sepsis, septic shock, and resulting organ failure appear as the most common cause of death in intensive care medicine. Inflammatory mediators (interleukin-6/IL-6), cell adhesion molecules (intercellular adhesion molecule-1/ICAM-1, vascular cell adhesion molecule-1/VCAM-1), and redox active substances (manganese superoxide dismutase/MnSOD, macrophage migration inhibitory factor/MIF) must be considered to be central hubs in the inflammatory process. However, their exact pathophysiologic function and prognostic value are still poorly understood. - Materials and Methods - In total, 133 individuals (87 patients with severe sepsis or septic shock, 28 postoperative patients after major abdominal surgery, 18 healthy volunteers) were enrolled in the study. Blood samples from septic patients were collected within 24 h after the time of sepsis diagnosis, and 48 and 120 h later; samples from healthy volunteers were collected once, and samples from postoperative patients once immediately after surgery. In all patients we measured plasma levels of IL-6, sICAM-1, sVCAM-1, MnSOD, and MIF using enzyme linked immunosorbent assay (ELISA) kits. - Results - Healthy volunteers and postoperative patients showed comparable levels of cell adhesion molecules. Furthermore, their redox system was activated in a comparable manner, whereas in postoperative patients IL-6 was significantly elevated. Plasma levels of inflammatory mediators, cell adhesion molecules and redox active substances were significantly elevated in septic patients. In patients with sepsis who had died, plasma levels of MIF and MnSOD were significantly elevated in comparison with survivors. - Conclusions - Our results therefore demonstrate that redox active substances may play an important role in the septic inflammatory response. MIF and MnSOD appear to be early predictors for survival in septic patients.
Gesehen am 24.02.2023